A PRELIMINARY STUDY ON AQUIFER IDENTIFICATION BASED ON GEO-ELECTRICAL DATA IN BANDA ACEH, INDONESIA - Didik Sugiyanto; Ibnu Rusydy; Marwan Marwan; Dian Mutia Hidayati; Asrillah Asrillah (Universitas Syiah Kuala, 2018)
The aquifers exploration has been conducted at the western part of Banda Aceh, Indonesia. This research aims to explore the aquifer layer beneath the surface and to obtain the cross-section model of the aquifer. The Vertical Electrical Sounding (VES) method was applied to investigate the aquifer layer. The VES method worked as the current penetrated into the ground using of two electrodes and the potential response due to its current being measured by another two electrodes. Ten grid points of VES has performed in western part of Krueng Aceh of Banda Aceh using the ARES (Automatic Resistivity Meter). The Res1Dinv and curve matching computer software used in VES data processing and analysis. The result shows the resistivity value of aquifer in Banda Aceh city at the range of 1 – 12 Ωm for freshwater, and 0.1 – 0.6 for brackish water layer. The first aquifer (water table) found at a depth of 0.5 to 2 meters beneath the surface. The 2-meters water table mostly located near the coastal zone or downstream zone of Krueng Aceh basin and shallow depth of 0.5 meters on the upstream. More than one aquifer layers were found beneath the surface, they were separated by aquitard layer consisting of silt to clay layers.